Impact of Agricultural Transformation on Tribal Heritage in Modern Chhattisgarh - Sinha, Sujita (Journal of Advanced Research in Humanities and Social Sciences, 2025)
The state of Chhattisgarh, rich in tribal culture and heritage, has witnessed significant agricultural transformations in recent decades. These shifts, driven by modernization, policy changes, and market forces, have had profound and multifaceted impacts on the traditional ways of life, cultural practices, and social structures of its tribal communities. This article delves into the intricate relationship between agricultural transformation and tribal heritage in modern Chhattisgarh, examining both the opportunities and challenges that have emerged. It analyzes the changes in land ownership patterns, traditional farming practices, food systems, and the transmission of indigenous knowledge. Furthermore, it explores the influence of commercial agriculture on tribal art, music, rituals, and social customs, considering the potential for both cultural erosion and adaptation. By examining ten key aspects of this dynamic interplay, supported by scholarly quotations and references, this article aims to provide a comprehensive understanding of how agricultural modernization is reshaping the tribal heritage of Chhattisgarh and to highlight the urgent need for culturally sensitive and sustainable development approaches that respect and preserve the unique identity of these communities. The analysis underscores the importance of recognizing tribal perspectives and ensuring their active participation in shaping their future in the face of ongoing agricultural change.